Juventude urbana e redes sociais em Moçambique: a participação política dos conectados desamparados - Tsandzana, Dércio (Comunicação e Sociedade, 2018)
Nos últimos 10 anos, os estudos sobre a participação política por intermédio das redes sociais marcam o debate na área dos estudos dos média. Em Moçambique, de forma particular, e no mundo, de forma geral, a juventude representa o centro galvanizador que encontra no uso das redes socias uma ferramenta quase ideal de expressão sobre as suas frustrações decorrentes da sua situação de gritante miséria social – desemprego e incerteza de vida constante a que os jovens se encontram expostos. Com o presente artigo, pretendemos analisar o papel das redes sociais, concretamente o Facebook, no engajamento político e social da juventude urbana em Moçambique, considerando um horizonte que abarca os últimos quatro anos, 2014-2017. Como resultado, concluímos que embora a sua expansão nos últimos anos, as redes sociais ainda não podem ser consideradas, no seu todo, como espaços que permitam uma efectiva participação política da juventude, decorrente do facto de a internet ser menos abrangente, por um lado, e do fraco interesse da juventude em questões políticas em Moçambique, por outro. EN: In the last 10 years, studies on political participation through social networks have marked the debate in the field of media studies. In Mozambique, particularly, and in the world, in general, youth represent the galvanizing centre that finds in the use of social networks an almost ideal tool of expression about their frustrations due to their situation of blatant social misery – unemployment and constant life uncertainty to which youth are exposed. With this article, we intend to analyse the role of social networks, specifically Facebook, in the political and social engagement of urban youth in Mozambique, considering a timeline that covers the last four years, 2014 to 2017. As a result, it is concluded that, despite the expansion of social networks in recent years, they cannot yet be considered as spaces for effective political participation by youth, due to the fact that the internet is less comprehensive, on the one hand, and the weak youth interest in political issues in Mozambique, on the other.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - central / centro; G - south / sul; GD - Beira; GP - Maputo; GP - Sofala; L - portuguese / português; citizenship & participation / cidadania e participação; decentralization / descentralização; youth / juventude

Manual de Implementação do Cartão de Pontuação Comunitária pelo Programa CEP - Programme, Citizen Engagement (2018)
O Programa CEP – Cidadania e Participação é um programa de responsabilização social que tem como objectivo contribuir para a melhoria da qualidade dos serviços de saúde e educação, nos lugares onde o programa é implementado. A visão do CEP é a de cidadãos a beneficiarem de serviços públicos de educação e saúde apropriados e de qualidade, onde são tratados com respeito e dignidade. A abordagem utilizada ao nível local é a de promover a participação e o engajamento dos cidadãos e comunidades com os provedores de serviços das unidades de serviço de nível primário (as escolas primárias e os centros de saúde), através da metodologia do Cartão de Pontuação Comunitária (CPC), para a identificação e solução de questões de qualidade e desempenho. Este documento debruça-se sobre o CPC e foi concebido com o objectivo de dar a conhecer e explicar, passo a passo, como esta metodologia é implementada pelo CEP. É dirigido a praticantes, pessoas e organizações, que estejam a implementar o CPC, ou a considerar fazê-lo, em contextos similares. O documento é resultado de processos contínuos de reflexão, aprendizagem e refinamento da forma de trabalhar e das abordagens e instrumentos usados. O Manual de Implementação do Cartão de Pontuação Comunitária pelo CEP consta de duas partes. A parte I é constituída por uma apresentação geral do CPC, as suas etapas e o que se faz em cada etapa, e um guião detalhado do processo, com indicação dos principais momentos e intervenientes. A parte II apresenta o conjunto das fichas utilizadas no processo do CPC como foi implementado pelo CEP.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; ⛔ No DOI found

Moçambique - recessão antes do boom: Reflexões sobre picos de investimento e novas fontes de gás - Roe, Alan (2018)
Este artigo surge na sequência de um artigo anterior onde se considerou em termos gerais muitas das questões que Moçambique enfrenta hoje em dia na gestão dos seus novos recursos extractivos. Em primeiro lugar descreve-se o pico de investimento já desencadeado pelas novas descobertas de gás em Moçambique. Depois apresenta-se em resumo alguma da literatura mais recente sobre os efeitos desses picos noutros países e contextos. De seguida analisam-se os principais aspectos dos resultados económicos decepcionantes testemunhados até 2018, e analisase selectivamente algumas das implicações destes resultados nas políticas futuras. O artigo conclui explorando a epidemiologia de um grande pico do investimento público — uma questão que tem relevância para o pico adicional que ainda é esperado. Ao seguir esta sequência de argumento, procura-se igualmente compreender melhor diversas questões fundamentais de política geral que surgem no contexto das grandes descobertas de novos recursos.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Mozambique - bust before boom: Reflections on investment surges and new gas - Roe, Alan R. (WIDER Working Paper Series, 2018)
This paper is a sequel to an earlier paper that looked in broad terms at many of the issues that Mozambique faces today in managing its new extractive resources. The paper first describes the investment surge that has already been prompted by new gas discoveries in Mozambique. It then summarizes some of the more recent literature that has examined the effects of such surges in other country contexts. It next examines the main aspects of the disappointing economic outcomes that have so far been seen through 2018, and selectively analyses some of the implications of these outcomes for future policy. The paper concludes by exploring the epidemiology of a large public investment surge—an issue that has relevance for the further surge that is still anticipated. In following this sequence of argument, the paper also throws light on a number of critical general policy questions that arise in the context of major new resource discovery.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

Understanding Decentralization in Mozambique with a Ziblatt-Mann Framework - Ferrant, Coline (International Relations, 2018)
In this article, Ferrant examines decentralization reforms in Mozambique since 1994, through an analysis of primary and secondary sources, and a framework that draws from the theses of political scientist Daniel Ziblatt and sociologist Michael Mann.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; decentralization / descentralização; ⛔ No DOI found

‘Goats eat where they are tied up’: illicit and habitual corruption in Mozambique - Tvedten, Inge; Picardo, Rachi (Review of African Political Economy, 2018)
The article shows that corruption is structural and omnipresent in Mozambican society, eﬀectively legitimising corrupt practices at all levels. Using an anthropological approach, it argues that smallscale corruption has the most immediate eﬀects for the urban and rural poor and is so common that it has become an integrated part of daily life, or ‘habitual’. While most of the poor relate to corruption through tacit acceptance and acts of compliance, its practical implications are most severe for the very poorest, who cannot aﬀord to take part in corrupt exchanges and are excluded from vital social relationships and social services. A few case studies included re: Northern Moz.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; corruption / corrupção; institutions / instituições; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social

The Construction Sector in Mozambique - Cruz, António S.; Fernandes, Francisco; Mafambissa, Fausto J.; Pereira, Francisco; Cruz, António S.; Fernandes, Francisco; Mafambissa, Fausto J.; Pereira, Francisco (2018)
Abstract: The construction sector value added in Mozambique grew at an average annual rate of 12.8 per cent in 1993–2015. Investment in the basic infrastructure of health, education, and housing improved families’ and communities’ living conditions. Investment in roads, communications, and office facilities boosted economic activities and reduced transaction costs. Construction value added grew by only 1.1 per cent in 2016. Challenges ahead include enabling a business environment conducive to expanding small and medium companies in the formal sector; reducing production costs and increasing international competitiveness; improving the prioritizing and programming of public investments; and improving training systems and basic public infrastructure quality.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; infrastructure / infrastrutura

What are the prospects for Mozambique to diversify its economy on the back of 'local content'? - Dietsche, Evelyn; Esteves, Ana Maria (WIDER Working Paper Series, 2018)
In recent years, Mozambique has made international headlines for the significant hydrocarbon deposits found offshore. These have increased the country's extractive resource endowments, in addition to its mining and onshore natural gas sector. It is expected that these industries will contribute to economic diversification and social development, not least by means of procuring locally produced goods and services and hiring Mozambicans. A key factor to achieve this is building domestic capital?in people, institutions, and infrastructure.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); ⛔ No DOI found

Islamic Insurgency in Cabo Delgado: Extractive Industry, Youth Revolt and Global Terrorism in Northern Mozambique - Bonate, Liazzat J. K. (The University of the West Indies, St Augustine, 2018)
The violent insurgency in northern Mozambican province of Cabo Delgado, that started in October 2017 and is still ongoing, caught the government of the country and the public by surprise. Although this insurgency remains largely unexplored and little understood, the only study done so far has suggested that it is being carried out by Muslim youth connected to Islamic radicalism, in particular to the Harakat alShabaab of Somalia and its offshoots in Kenya, Tanzania, and as far as DRC.1 Islam has a long history in Mozambique, since probably the eighth century.2 According to the 2017 National Population Census, Muslims account for about 18% of the total population the country and 58% of the Cabo Delgado inhabitants. However, Mozambique had never had any visible Islamist radical political movement before.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; youth / juventude

The Political Economy of Social Protection in Mozambique - Buur, Lars; Salimo, Padil (SSRN Electronic Journal, 2018)
In the view of international donors, multilateral organisations and government officials, social protection in Mozambique benefits from strong government commitment to it. Their argument is that, in contrast to many African countries, the government has demonstrated a level of commitment and support to social protection that is quite unprecedented. This view relies on the fact that more than 90 per cent of the budget allocated to the implementation of social protection programmes comes from the state budget and that, even within the complex context of the financial crisis that has devastated the economy since 2013, social protection has continued to receive special attention from the government in its budget allocations. Based on a political economy analysis, this paper challenges the common narrative of social protection in Mozambique, by arguing that social protection has been used as a means to mobilise resources from international agencies, in order to ensure the political survival of the Frelimo government. The paper argues that government support of social protection emerged as a reaction to the poor performance of poverty-reduction initiatives, becoming also a mechanism to overcome social protests after the 2008 and 2010 riots in Mozambique, which threatened to jeopardise the stability of the regime and its reproduction of power.
Keywords: *indexed; *tagged; Ethnographic Studies; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Social Protection PEA; development partners / parceiros de cooperação; social protection / proteção social

Progress in Mozambique: Changes in the availability, use, and quality of emergency obstetric and newborn care between 2007 and 2012 - Augusto, Orvalho; Keyes, Emily E.; Madede, Tavares; Abacassamo, Fátima; de la Corte, Pilar; Chilundo, Baltazar; Bailey, Patricia E. (PLOS ONE, 2018)
Introduction Maternal mortality in Mozambique has not declined significantly in the last 10–15 years, plateauing around 480 maternal deaths per 100,000 live births. Good quality antenatal care and routine and emergency intrapartum care are critical to reducing preventable maternal and newborn deaths. Materials and methods We compare the findings from two national cross-sectional facility-based assessments conducted in 2007 and 2012. Both were designed to measure the availability, use and quality of emergency obstetric and neonatal care. Indicators for monitoring emergency obstetric care were used as were descriptive statistics. Results The availability of facilities providing the full range of obstetric life-saving procedures (signal functions) decreased. However, an expansion in the provision of individual signal functions was highly visible in health centers and health posts, but in hospitals, performance was less satisfactory, with proportionally fewer hospitals providing assisted vaginal delivery, obstetric surgery and blood transfusions. All other key indicators showed signs of improvements: the institutional delivery rate, the cesarean delivery rate, met need for emergency obstetric care (EmOC), institutional stillbirth and early neonatal death rates, and cause-specific case fatality rates (CFRs). CFRs for most major obstetric complications declined between 17% and 69%. The contribution of direct causes to maternal deaths decreased while the proportion of indirect causes doubled during the five-year interval. Conclusions The indicator of EmOC service availability, often used for planning and developing EmONC networks, requires close examination. The standard definition can mask programmatic weaknesses and thus, fails to inform decision makers of what to target. In this case, the decline in the use of assisted vaginal delivery explained much of the difference in this indicator between the two surveys, as did faltering hospital performance. Despite this backsliding, many signs of improvement were also observed in this 5-year period, but indicator levels continue below recommended thresholds. The quality of intrapartum care and the adverse consequences from infectious diseases during pregnancy point to priority areas for programmatic improvement.
Keywords: G - Mozambique / Moçambique; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Power, conflict and natural resources: The Mozambican crisis revisited - Macuane, José Jaime; Buur, Lars; Monjane, Celso Marcos (African Affairs, 2018)
This article explores how the present socio-economic crisis in Mozambique is linked to the prospects of natural resource windfalls for the country. Drawing on the political settlement approach, it explores how the distribution of power both within and outside the ruling elite is structured and consequently how the underlying political processes have been shaped by the expectations of natural resource windfalls. The article argues that the present socio-economic crisis in Mozambique is not due to national resource assets in themselves. Instead, the political and economic downturn in Mozambique should be understood as a manifestation of how the political settlement has been organized and rent mobilization controlled by the ruling elite. To understand how the prospect of rents from natural resource sectors have influenced the political settlement, we have argued that one has to look at the dynamics of power both within and outside the ruling elite and the incentives they create for elites to use the control of power and access to economic benefits to achieve narrow and short-term gains rather than inclusive and longer-term goals.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict / conflito; extractive industries / indústrias extractivas; natural resources / recursos naturais; power / poder

‘When helpers hurt’: women’s and midwives’ stories of obstetric violence in state health institutions, Colombo district, Sri Lanka - Perera, Dinusha; Lund, Ragnhild; Swahnberg, Katarina; Schei, Berit; Infanti, Jennifer J.; Darj, Elisabeth; Lukasse, Mirjam; Bjørngaard, Johan Håkon; Joshi, Sunil Kumar; Rishal, Poonam; Koju, Rajendra; Pun, Kunta Devi; et al. (BMC Pregnancy and Childbirth, 2018)
The paper explores how age, social position or class, and linguistic and cultural background intersect and place women in varying positions of control and vulnerability to obstetric violence in state health institutions in Colombo district, Sri Lanka. Obstetric violence occurs during pregnancy, childbirth and the immediate postpartum period; hence, it is violence that directly affects women. The authors aim to break the traditional culture of silence around obstetric violence and bring attention to the resulting implications for quality of care and patient trust in obstetric care facilities or providers.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Contract farming for improving smallholder incomes: What can we learn from effectiveness studies? - Ton, Giel; Vellema, Wytse; Desiere, Sam; Weituschat, Sophia; D'Haese, Marijke (World Development, 2018)
Contract farming is a sales arrangement between a farmer and a firm, agreed before production begins, which provides the farmer with resources or services. Many governments and donors promote contract farming as part of agricultural development policies. However, there is serious concern whether smaller farmers can benefit from these arrangements. This paper presents the results of a systematic review that analysed the evidence in the literature on income effects for smallholders. The review included all studies with an econometric design to reduce selection bias in effect estimates. The meta-analysis covered 26 empirical instances of contract farming in 13 developing countries. The contracts varied widely, with varying service packages provided by the firm to the farmers. Using truth table analysis, we explored combinations of services associated with relatively high or relatively low income effects. The meta-analysis resulted in an overall pooled average effect size of 38%. However, we show that there are publication and survivor biases. Non-significant effects are systematically underreported. Moreover, all studies assessed the effectiveness of the contractual arrangement when these had already survived the start-up problems. Both sources of bias lead to an overestimation of the average income effect. The findings point to the need for substantial income effects for contract farming arrangements to survive over time. Both firms and farmers face risks; for example, farmers may side-sell products after having received the services from the firm. The most effective contractual arrangements included a price premium, especially when there was no farmers’ organisation to broker the contract between the farmer and the firm. We show that smallholders can benefit from the contractual arrangement. However, the poorest farmers are rarely included; we show that, in 61% of the cases, the contract farmers had significantly larger landholdings or more assets than the average farmers in the region.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture - agricultural markets / agricultura - mercados agrícolos; agriculture / agricultura

Inverted State and Citizens’ Roles in the Mozambican Health Sector - Dias, Jose; Tomé, Tassiana (IDS Bulletin, 2018)
This article aims to understand the inversion of roles between the state and citizens, by exploring its historical roots and current implications for processes of social accountability in Mozambique, particularly in the health sector. This is a practice-based reflection grounded in the evidence collected through the implementation of Community Scorecards in the health sector in 13 districts of Mozambique. The evidence has revealed a transfer of responsibilities from local governance institutions and service providers to the communities; diluting the frontiers between the state and citizens’ duties and rights, resulting in the inversion of roles. This inversion results in the minimisation of the state’s performance of its duties and accountability in the health sector to respond to local communities’ needs, allegedly due to the lack of financial resources. It also leads to the overburdening of local communities, who assume the responsibility of meeting their own demands, risking participation fatigue.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; Important; L - english / inglês; Northern PEA; accountability / responsabilização; health / saúde

The Impact Analysis of ASEAN-Japan Comprehensive Economic Partnership (ajcep) for Trade Flow and Economic Growth’s Convergence - Darsono, Tri Arifin; Hakim, Dedi Budiman; Rindayati, Wiwiek (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2018)
Free Trade Area (FTA) between ASEAN and Japan, which is called ASEAN-Japan Comprehensive Economic Partnership (AJCEP), has been established since 2002 as goods and services flow gateway. AJCEP plays an important role to bring the development, economic security, and economic power. It can also boost the economic growth among member of ASEAN-Japan. The objectives of this research were to analyze the factors that can influence the ASEAN-Japan countries import with non-member, to analyze the occurrence of trade creation and trade diversion in trading sector among ASEAN-Japan countries with non-member, and to analyze the occurrence of economic growth's convergence in ASEAN-Japan Comprehensive Economic Partnership (AJCEP) not only among ASEAN-Japan countries, but also with non-member trading partners. The Gravity Model was used to analyze import factors and observing the occurrence of trade creation or trade diversion. The GMM model was used to observe the convergence of economic growth. The research are used Panel data methods with periods 2000 until 2013 in 13 countries.      The research found that the coefficient values in trade creation and trade diversion dummy were 0.92 and 31.41. The positive value in trade creation and trade diversion indicated the occurrence of trade creation in the import flow among ASEAN-Japan countries and non-member trading partners, as well as finding the convergence of economic growth among ASEAN-Japan countries. The convergence level was of 0.0153417 can be interpreted that the velocity to reach steady state condition was 2.00 percent per year with the assumption of ceteris paribus. The duration to reach convergence condition or half life of convergence was about 34 years. The research found the trade creation from AJCEP agreement and the occurrence of economic growth’s convergence. Based on the result, Indonesian government would likely to make relationships among countries member and non-member to invest in real sector that will boost economic growth in Indonesia. Keywords: ASEAN-Japan Comprehensive Economic Partnership, Growth’s convergence, gravity model, GMM model, trade creation, trade diversion.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Disrespectful and abusive treatment during facility delivery in Tanzania: a facility and community survey - Kruk, Margaret E; Kujawski, Stephanie; Mbaruku, Godfrey; Ramsey, Kate; Moyo, Wema; Freedman, Lynn P (Health Policy and Planning, 2018)
Although qualitative studies have raised attention to humiliating treatment of women during labour and delivery, there are no reliable estimates of the prevalence of disrespectful and abusive treatment in health facilities. We measured the frequency of reported abusive experiences during facility childbirth in eight health facilities in Tanzania and examined associated factors. The study was conducted in rural northeastern Tanzania. Using a structured questionnaire, we interviewed women who had delivered in health facilities upon discharge and re-interviewed a randomly selected subset 5–10 weeks later in the community. We calculated frequencies of 14 abusive experiences and the prevalence of any disrespect/abuse. We performed logistic regression to analyse associations between abusive treatment and individual and birth experience characteristics. A total of 1779 women participated in the exit survey (70.6% response rate) and 593 were re-interviewed at home (75.8% response rate). The frequency of any abusive or disrespectful treatment during childbirth was 343 (19.48%) in the exit sample and 167 (28.21%) in the follow-up sample; the difference may be due to courtesy bias in exit interviews. The most common events reported on follow-up were being ignored (N = 84, 14.24%), being shouted at (N = 78, 13.18%) and receiving negative or threatening comments (N = 68, 11.54%). Thirty women (5.1%) were slapped or pinched and 31 women (5.31%) delivered alone. In the follow-up sample women with secondary education were more likely to report abusive treatment (odds ratio (OR) 1.48, confidence interval (CI): 1.10–1.98), as were poor women (OR 1.80, CI: 1.31–2.47) and women with self-reported depression in the previous year (OR 1.62, CI: 1.23–2.14). Between 19% and 28% of women in eight facilities in northeastern Tanzania experienced disrespectful and/or abusive treatment from health providers during childbirth. This is a health system crisis that requires urgent solutions both to ensure women’s right to dignity in health care and to improve effective utilization of facilities for childbirth in order to reduce maternal mortality.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde

Challenges and Strategies in Place-Based Multi-Stakeholder Collaboration for Sustainability: Learning from Experiences in the Global South - Ayala-Orozco, Bárbara; Rosell, Julieta A.; Merçon, Juliana; Bueno, Isabel; Alatorre-Frenk, Gerardo; Langle-Flores, Alfonso; Lobato, Anaid (Sustainability, 2018)
Addressing complex environmental problems requires the collaboration of stakeholders with divergent perspectives, a goal that is challenged by diverse factors. Challenges hindering multi-stakeholder collaboration (MSC) for sustainability have previously been addressed in the context of transnational partnerships. However, less is known regarding how place-based MSC operates, especially in the context of the Global South. To contribute to addressing the factors that hinder place-based MSC for sustainability in the Global South, we analyzed 38 MSC projects spanning diverse ecological and social contexts across Mexico. In a series of participatory workshops, 128 stakeholders from academia, government, business, local communities, and civil society organizations discussed factors that hinder place-based MSC and co-constructed strategies to strengthen collaboration. Some challenges coincided with those identified in previous studies (e.g., divergent visions, inadequate project planning), whereas other concerns that have not been commonly regarded as important emerged as crucial obstacles for MSC. We discuss these challenges in the context of areas of limited statehood and point to the traditions of popular education and participatory action research as a source of valuable tools for place-based MSC. We identify strategies capable of addressing diverse challenges, a result that could aid prioritizing resource allocation to strengthen MSC.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; collaboration / colaboração

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

The Importance of Lender-borrower Relationships to the Availability of Small and Micro Credit: Case Study on Indonesian Kredit Usaha Rakyat Loans - Suryani, Embun (International Journal of Economics and Financial Issues; Mersin, 2018)
This study aims to examine how the relationships between a borrower and his potential lender affect the decisions of potential lender whether or not to provide or extend funds to the borrower. The author explores the available literature and original fieldwork to create a framework to capture this relationship. The study employs descriptive qualitative data to analyze and examine the research questions. The result shows that borrowers who build their commercial transactions with their lender on intensive relationships are more likely to receive and extend loans. The relationship effects arise because it motivates both lender and borrower to share private resources and facilitate access to loan opportunities, but does not influence the price of loans. To sum up, the lender-borrower relationships are valuable and seem to operate through quantities, trust and the length of these relationships. Furthermore, these relationships are more appropriate to be implemented for small and micro-lending.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

The Performance of Indonesia’s Public Credit Guarantee Scheme for MSMEs: A Regional Comparative Perspective - Tambunan, Tulus T.H. (Journal of Southeast Asian Economies, 2018)
Access to finance has been a key constraint for Indonesia’s micro, small and medium enterprises (MSMEs) that lack tangible assets to be used as collateral. Consequently, credit guarantee schemes (CGSs) are important instruments to meet MSMEs’ financial needs. This paper examines the effectiveness of the KUR (community business credit), a partial public CGS in Indonesia, by comparing it with similar schemes in other ASEAN member states (AMS). The findings suggest that the KUR programme, despite its limited coverage, has been quite effective throughout the country. Some of the critical factors behind its success include: wide dissemination of the programme; simplicity of the application procedure; full participation and support from banks; and strong coordination between all stakeholders.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA